Musik Meningkatkan Konsentrasi Belajar Siswa Kelompok Peminatan MIPA - Firman, Salabila Nararya; Bramantyo, Triyono; Warsono, Warsono (IDEA: Jurnal Ilmiah Seni Pertunjukan, 2024)
Teenagers, especially high school students, often face distractions while studying. The unrestricted use of social media also affects their study concentration. Additionally, pressures from various sources and the transition from being a student to a university student add to the burden of responsibilities. As a result, most students experience sustained stress, negatively impacting their academic performance. To address this, students seek media to enhance their study concentration, and one commonly used medium is music. Music is believed to improve study concentration, subsequently positively influencing academic outcomes. Research indicates that the use of music has a particularly positive impact on the STEM (Science, Technology, Engineering, and Mathematics) study group. Compared to other study groups, students majoring in STEM tend to achieve better results in using music as a tool to enhance study concentration. It is noted that the STEM study group experienced an average increase of 7 points from the pre-test to the post-test, while other study groups had an average increase of 6 points.